OPTIMAL LINEAR CONTROL APPLIED TO A NON-IDEAL CAPSULE SYSTEM WITH UNCERTAIN PARAMETERS - Roéfero, Luiz Gustavo Pereira; Chavarette, Fábio Roberto; Outa, Roberto; Merizio, Igor Feliciani; Moro, Thiago Carreta [UNESP]; Mishra, Vishnu Narayan (My University, 2022)
The design of mechanical structures aims to meet criteria, to-gether with the safety of operators and lives in the vicinity of the equipment. Thus, there are several cases that meeting the desired specification causes the mechanical device to perform unstable and, sometimes, chaotic behav-ior. In these cases, control methods are applied in order to stabilize the device when in operation, aiming at the physical integrity of the component and the device operators. In this work, we will develop a study about the influence of a controller applied in a non-ideal capsule system operating with uncertain parameters, being non-existent in the literature. For this, two initial conditions were used: one that the capsule starts from rest and another that it is already in motion. Thus, the effectiveness of the controller can be assessed in both initial conditions, restricting the movement of the internal vibration-impact system to the capsule.
Keywords: LQR Control; non-Ideal Systems; Uncertain Parameters